Aerobic Vaginitis Induced by Escherichia coli Infection During Pregnancy Can Result in Adverse Pregnancy Outcomes Through the IL-4/JAK-1/STAT-6 Pathway - Fan, Chong; Dai, Youjin; Zhang, Lei; Rui, Can; Wang, Xinyan; Luan, Ting; Fan, Yuru; Dong, Zhiyong; Hou, Wenwen; Li, Ping; Liao, Qinping; Zeng, Xin (Frontiers in Microbiology, 2021)
Aerobic vaginitis (AV) can occur if normal vaginal microflora are dominated by aerobic bacteria, seriously affects not only female health, but also fetal health while they are pregnant. Besides, pregnant status also aggravates the symptoms and consequences of the infection. Here, we infected pregnant BALB/c mice with Escherichia coli on embryonic day 4.5 (E4.5) (study group), and administered an equivalent volume of phosphate-buffered saline in another cohort of pregnant mice (control group). We recorded the weight of pregnant mice and their fetuses. The maternal and fetal weight of the study group decreased in comparison with that of the control group, whereas the weight of placenta increased in the study group. Then, five genes with significant upregulation and 15 genes with downregulation were screened. Expression of interleukin 4 (IL-4) mRNA in the study group decreased to 18.5%. Enzyme-linked immunosorbent assay results showed IL-4 expression in mouse plasma declined in the study group at E11.5 and E18.5. mRNA expression of chemokine (c-c motif) ligand (CCL)-17, CCL-22, CCL-24, IL-4, Janus Kinase (JAK)-1, signal transducer and activator of transcription (STAT)-6, and GATA-3 showed significant downregulation in placental and uterine tissues. Flow cytometry of primary decidual macrophages (DMs) revealed more M1-like macrophages in the study group. And after addition of IL-4 to DMs, more M1 macrophages polarized to M2 type macrophages. We did not discover bacteria existed in mouse placentas. Our study affords a feasible method for exploring and managing AV during pregnancy.